Personal finance: a statistical analysis of the habits and behaviours of the South African consumer - Rajak, Ehsaan (Department of Statistical Sciences, 2025)
Understanding consumer spending behavior and the efficacy of budget setting is crucial in managing personal finances. This dissertation employs clustering methodologies and statistical models to explore the intricate dynamics of financial habits and their relationship with budget establishment using longitudinal spending data from the 22seven platform. The initial chapters delve into the analysis of consumer spending behavior through various clustering techniques, unveiling fundamental drivers of spending patterns. While highlighting the role of spending control in distinguishing consumer clusters, the study emphasizes its correlation with wealth creation potential. Subsequently, the investigation into the impact of budget setting on expenditure habits reveals compelling evidence. Individuals who set a budget exhibited a significant reduction in spending, indicating an average decrease of approximately 38% compared to non-budget setters. However, limitations in observational data analysis, including incomplete financial account linkage and potential sample bias, caution against drawing absolute conclusions. This dissertation underscores the complexity of consumer financial decision-making, calling for continued exploration and refinement of methodologies to better grasp the nuanced interplay between budget setting and expenditure patterns. While providing valuable insights, this study serves as a stepping stone for future research, encouraging a deeper understanding of effective spending control, the balance between consumption and savings, and the broader efficacy of budgeting in managing overspend.